Roles of Events for Local Development: The Case of Dessie And Kombol-cha Cities: Research article - Getnet Ambaw, Zelalem; Fentaw Nigatu, Tesfaye (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2023)
This study aims to assess the impact of events on local development in Dessie and Kombolcha towns. The study employed a mixed research approach, utilizing a descriptive research design. Data was collected from 136 participants through questionnaires, and interviews were conducted with various sectors including culture and tourism offices, hotels, sports offices, religious institutions, cultural clubs, cinemas, and other government and non-governmental organizations. The findings reveal that local communities have a positive attitude towards event development. Religious festivals, trade fairs, and conferences were types of events in these towns. The results indicate that 61.2% of respondents believe that events play a significant role in boosting the local economy, while 70.6% perceive events as having a significant positive impact on expanding cultural perspectives. The study found that 88.5% of respondents believe that events have the potential to maximize tax revenue for local socioeconomic development. Events also contribute to the advancement of cultural performances for both hosts and guests. However, there are several challenges hindering the development of the event industry as a tourism business, such as low promotional efforts, a limited number of conference centers, low community awareness, lack of experience among businesses in organizing events, and inadequate coordination among stakeholders. To overcome these challenges and stimulate local development, it is crucial to promote and develop the event industry as a catalyst. This requires creating an enabling environment and providing external support. Additionally, strong local governance should be developed to effectively manage and leverage the potential of events.